Sigmoido-rectal intussusception anastomosis in the Altemeier procedure for complete rectal prolapse: preliminary results of a new technique - Wang, Benjun; Han, Weiwei; Zhai, Yuze; Shi, Renjie (Frontiers in Surgery, 2024)
Purpose: Our research introduces an innovative surgical approach, combining the Altemeier Procedure with Sigmoido-rectal Intussusception Anastomosis, effectively reducing recurrence, minimizing complications, and improving postoperative anal function in rectal prolapse patients. Materials and Methods: This retrospective study, conducted at tertiary referral hospitals including Shandong University of Traditional Chinese Medicine's Affiliated Hospital, Linyi People's Hospital, and Pingyi People's Hospital, examined data from patients undergoing conventional Altemeier surgery or Altemeier combined with Sigmoido-rectal Intussusception Anastomosis. Analyzing hospitalization and follow-up data from January 2009 to December 2022, the study focused on prolapse recurrence, complications, and anal function as primary outcome indicators across these three study centers. Results: In the study, both groups had an average follow-up of (12.5±2.41) months, and only two traditional group patients experienced mortality. Recurrence rates significantly differed, with 26.47% in the traditional group and 1.54% in the modified group (P<0.001). The modified group showed no perioperative anastomotic dehiscence, contrasting with a 13.24% occurrence in the conventional group (P=0.003). Primary complications in the modified group included anastomotic hemorrhage, with rates of 17.65% and 6.15% in the traditional and modified groups, respectively (P=0.077). At 12 months postoperatively, both groups improved in anal manometry parameters and the Wexner anal incontinence score. Resting pressure was significantly lower in the traditional group (32.50±1.76 mmHg) than in the modified group (33.24±2.06 mmHg) (P=0.027), while the extrusion pressure was higher in the modified group (64.78±1.55 mmHg) than the traditional group (62.85±2.30 mmHg) (P<0.001). The Wexner anal incontinence score was significantly lower in the modified group (2.69±1.65) than in the traditional group (3.69±1.58, P=0.001). Conclusion: This retrospective study affirms that adding Sigmoido-rectal Intussusception Anastomosis to the Altemeier procedure reduces recurrence and complications. While both approaches enhance postoperative anal function in complete rectal prolapse patients, the combined method, particularly with Sigmoido-rectal Intussusception Anastomosis, proves more effective.